Effect of Trust, Risk Perception and Perception Usability on User Satisfaction of Mobile Banking In Palopo City - Mernik Ennhyy; Rahmad Solling Hamid; Muhammad Ikbal (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose :Research is to analyze the influence of trust, perceived risk, and perceived usefulness on mobile user satisfaction. banking ( BRImo ) in Palopo City. Methodology : used in this study is a quantitative approach with a survey method, where data was collected by distributing questionnaires to 160 respondents using a purposive sampling technique, then analyzed using the Partial Sample method. Least Squares-Structural Equation Modeling (PLS-SEM) with the help of SmartPLS . Results: This study show that trust and perceived usefulness have a positive and significant influence on user satisfaction, while perceived risk has a negative and significant influence on user satisfaction, with a coefficient of determination of 0.732. Findings of this study confirm that increasing trust and the benefits of using the application can increase user satisfaction, while high perceived risk can decrease satisfaction. Novelty This study lies in the combination of three main variables in one analysis model in the context of BRImo users in Palopo City with the PLS-SEM approach. Originality : This study is demonstrated through its focus on specific research objects and locations and providing the latest empirical evidence related to mobile user behavior. banking in the area. Conclusion : This study is that mobile user satisfaction Banking is significantly influenced by trust, perceived risk, and perceived usefulness, so banks need to improve security, reduce risk, and strengthen the benefits of services. This research paper : a quantitative empirical research.